Проблемы социализации личности в виртуальном пространстве - Колода, Д. Д. (ХНУРЕ, 2019)
Socialization of the individual is quite an actual problem of our time. Our time does not stand still, and, having entered the postmodern era, man began to perceive others and himself in a new way. This is due to the emergence of a large number of technologies. Internet socialization makes the personality of the changing and increasingly complex requirements, has a contradictory character - is manifested in the form of negative relationships.